Temporal dynamics and forecasting of respiratory viral infections during and after the SARS-CoV-2 pandemic (2020–2027): a multiplex PCR and ARIMA-based study - Koçer, İpek; Demirbakan, Hadiye; Aktaş, Ahmet (Frontiers in Microbiology, 2025)
IntroductionRespiratory viruses are the leading cause of acute respiratory tract infections in both children and adults, with significant morbidity and healthcare burden. Before the COVID-19 pandemic, these pathogens typically exhibited predictable seasonal circulation patterns. However, the pandemic markedly disrupted this seasonality, leading to reduced viral detection during lockdowns and unusual peaks in subsequent periods.ObjectiveThis study aimed to identify respiratory pathogens in LRTI patients using multiplex PCR and to assess changes in virus distribution during and after the COVID-19 pandemic across age groups.MethodsA total of 748 nasopharyngeal swab samples (one per patient) collected between March 2020 and November 2024 were retrospectively analyzed using the QIAstat-Dx Respiratory Panel, a multiplex PCR assay de tecting 19 respiratory viruses including SARS-CoV-2, influenza viruses, respiratory syncytial virus (RSV), and Rhinovirus/Enterovirus. Statistical analyses, including multivariate logistic regression, assessed viral positivity predictors. Additionally, the Autoregressive Integrated Moving Average (ARIMA) time-series model was used to evaluate trends and predict respiratory virus activity through 2027.ResultsThe cohort comprised 60.4% males and 39.6% females, with 14.4% pediatric (0–18 years) and 85.6% adult patients. Respiratory viruses were detected in 43.6% of samples, with significantly higher positivity in children (71.5%) compared to adults (40%) (p < 0.01). SARS-CoV-2 dominated during the pandemic (65.5% of positive cases), whereas post-pandemic viral circulation shifted toward other pathogens, notably Rhinovirus/Enterovirus (71.5%). Co-infections occurred more frequently in children (14.1%) than adults (2.7%) (p < 0.001). RSV re-emerged in late 2022 but was undetected in 2024, while influenza activity increased notably in early 2024. Multivariate analysis identified pediatric age as a strong independent predictor of viral positivity (OR: 3.68; 95% CI: 2.25–6.03).DiscussionFollowing the relaxation of public health measures, there was a marked resurgence of non- SARS-CoV-2 respiratory viruses, particularly in children, indicating a possible shift in viral epidemiology. These findings emphasize the critical need for ongoing surveillance and targeted interventions, especially in pediatric populations, to mitigate future respiratory viral disease burdens.